1999
DOI: 10.1146/annurev.physiol.61.1.193
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Natriuretic Peptide Secretion by the Heart

Abstract: Secreted by the heart, more specifically by atrial cardiomyocytes under normal conditions but also by ventricular myocytes during cardiac hypertrophy, natriuretic peptides are now considered important hormones in the control of blood pressure and salt and water excretion. Studies on natriuretic peptide secretagogues and their mechanisms of action have been complicated by hemodynamic changes and contractions to which the atria are constantly subjected. It now appears that atrial stretch through mechano-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 114 publications
2
37
1
Order By: Relevance
“…In previous studies with the teleost rainbow trout, endothelin-1 has been found to cause several short-term oscillations in blood pressure followed by a sustained hypertensive period (19,15,6). In mammals, it has been found that locally induced vasoactive agents, such as endothelin-1, mediate, in a paracrine fashion, part of the stretch-induced ANP secretion (29). Combined inhibition of endothelin and ANG II receptors has been reported to almost completely abolish the volume load-induced ANP release in vivo in rats (16).…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies with the teleost rainbow trout, endothelin-1 has been found to cause several short-term oscillations in blood pressure followed by a sustained hypertensive period (19,15,6). In mammals, it has been found that locally induced vasoactive agents, such as endothelin-1, mediate, in a paracrine fashion, part of the stretch-induced ANP secretion (29). Combined inhibition of endothelin and ANG II receptors has been reported to almost completely abolish the volume load-induced ANP release in vivo in rats (16).…”
Section: Discussionmentioning
confidence: 97%
“…The cardiac natriuretic peptides have been shown to be important for the regulation of the water and salt balance in both physiological and pathophysiological conditions in mammals; therefore, peptide hormones belonging to this family have been proposed to have an essential role in fish osmoregulation as well (9,10). In mammals, volemic stimuli are potent regulators of the cardiac natriuretic peptide release (25,36), whereas in the eel an increase in plasma osmolality rather than blood volume has been proposed to be a major regulator of eel atrial and ventricular natriuretic peptides (12). In the present study, we examined the effect of increased plasma volume and dehydration and enhanced osmolality on sCP in salmon.…”
Section: Discussionmentioning
confidence: 98%
“…In mammals, atrial stretch is the most widely recognized stimulus for ANP secretion (25,36). The increase of plasma volume, resulting in heart wall stretch, has been shown to elevate the circulating ANP concentration in a large number of animal species (1,12,14,26,37).…”
Section: Discussionmentioning
confidence: 99%
“…From the mechanistic point of view, these findings arise from pharmacological blockade of signaling implicating PLC in ANF release and hence, support the involvement of G␣ q and the previously reported tonic inhibition of ANF secretion by Ca 2ϩ . This ion, however, is required for normal basal as well as stimulated release by agonists such as ET-1 (50).…”
Section: Discussionmentioning
confidence: 99%